MANAJEMEN PENINGKATAN MUTU PENDIDIKAN - Roemintoyo, Roemintoyo (Jurnal Inovasi Pendidikan, 2010)
One of the problem faced by Indonesia is educational quality in every of schooling level. Educational quality in school is related with teacher because teacher is the primary factor in learning process. Therefore it is necessarily an effort to improve teacher professionalism in school. The effort to improve teacher professionalism is conducted through recruitment for the candidates through LPTK, knowledge improvement and teacher capability with advanced study or education and training and also learning quality improvement through teaching supervision by principle/school supervisor. To improve educational quality can be started from school using MPMBS concept. Indicator of educational quality one among the others is educational management system factor in which including professional educator training system.